Analisis Dukungan Psikologi Perawat Dan Keluarga Dengan Gangguan Harga Diri Rendah Pada Pasien Stroke - Nur Imanah Jannati; Yernita Sukma Ayu Hutagalung; Subang Aini Nasution (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2026)
Background: Ischemic stroke is one of the leading causes of death and disability, especially in the elderly population. The impact of stroke is not only limited to physical activity, but also greatly affects the psychosocial condition of the sufferer. From a psychological aspect, stroke sufferers often experience various complex emotional disorders. Research tends to be deep sadness, anger, disappointment, and feelings of helplessness. One of the significant psychosocial problems experienced by stroke survivors is a decrease in low self-esteem. Methods: The approach used in this study is a qualitative approach. The data source in this study came from informants. This research was conducted at Royal Prima Hospital, Jambi City. Results: Based on the results of the research that has been conducted, it was found that stroke patients experience various psychological changes due to physical limitations that arise after having a stroke. Family support is the most influential factor in the psychological condition of stroke patients. Families who always accompany patients are able to help patients accept sick conditions and increase patient morale during the rehabilitation process. However, the results of the study show that psychological support from nurses is still not fully optimal. Conclusion: Based on the results of the study, stroke patients experience psychological changes such as feeling embarrassed, insecure, feeling a burden on the family, withdrawing from the social environment, and losing their zest for life due to physical limitations. This condition shows that the stroke has an impact not only on the physical, but also on the psychological of the patient. Family support in the form of attention, motivation, affection, mentoring, and medical assistance is very helpful in increasing the patient's enthusiasm and confidence during rehabilitation. Nurses also play a role in the recovery process through health education, motivation, and treatment assistance. However, emotional support and therapeutic communication from nurses are still not optimal because services are more focused on medical measures.